Morphotectonic Analysis of Euphrates River Basin/ Iraq (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Morphological and morphotectonic analysis have been used to obtain information that influences basis. The study area includes the Euphrates river basin in Iraq. Tectonically this area within a Stable shelf, The Stable Shelf which covers the vast majority of the focal south and west of Iraq reaches out into Syria and Jordan and Southwards into Kuwait and Saudi Arabia. It is separated in Iraq into three considerable structural zones. Discrimination of morphotectonic indices of Euphrates basin by using sevenindices. The Euphrates basin (main basin) was divided into four sub-basin (s.b) Wadi Horan, Wadi Ubaiyidh, Shuab Hwaimy, and Shuab Qusair. Which has been completed for each drainage basin utilizing remote sensing and GIS techniques? So as to identify the tectonic activity, different indices including Drainage density (D), Sinuosity index (S), Hypsometric integral (HI), Drainage basin asymmetry (AF), Basin Shape (BS), Transverse Topographic Symmetry (T) and Active tectonic index (Iat). The study demonstrates that the intensity of tectonic activities in different parts of the basin and sub-basins are different. The values of Drainage density (D) main basin and sub-basins are in high classes which mean that the study area has resultant of slight or impermeable subsurface material, little vegetation as well as a good discharge for water and sediments. The Sinuosity index (S) of all study area are sinuous and its semi-equilibrium. Hypsometric integral (HI) of Horan, Ubaiyidh and shuab Hwaimy sub-basins shows high values of HI which means high rates of geological erosion while the shuab Qusair and main basin shows moderate of erosion rates, HI high values shows that study area is tectonically uplifted. According to the calculation of Drainage basin asymmetry (AF) the study area reflects inactive tectonic activity. The Basin Shape (BS) all of the basins are in third class and it reflects inactive tectonic activity. After computing Transverse Topographic Symmetry (T) index in the area of investigate, the outcome demonstrate that all the subbasins lie in low active tectonics except wadi Horan and the main basin was moderate active tectonics. Based on an Active tectonic index (Iat) all the basins were moderate active tectonics except Horan subbasin is active tectonically. These basins have evolved as a result of plate movements, subsidence, uplift and various erosional processes. The study shows the variable relationship between faulting and valleys but most of the trends of faults are subparallel to the Euphrates River. Faults orientations in the study area are parallel to NE-SW direction and NW-SE direction. And also the type of drainage network in the study area which is varied from dendritic to parallel with SW-NE trending and its indicate that study area may be structurally controlled.